PENGARUH MEDIA PAPAN LABIRIN TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA MATERI PENJUMLAHAN BERSUSUN KELAS I SDI KOTA UNENG - Cahyani, Nur; Rininelda Dua, Marsela; Dasrimin, Henderikus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning media play an important role in creating meaningful mathematics learning experiences for elementary school students. The use of appropriate instructional media is expected to improve students' understanding and learning outcomes, particularly in the topic of vertical addition. One learning medium that can support this process is the maze board. The objectives were to determine students' mathematics learning outcomes before and after the implementation of the maze board learning media and to analyze its effect on learning outcomes in the topic of vertical addition for first-grade students at SDI Kota Uneng. A quantitative approach was employed using a Pre-Experimental Design with the One Group Pretest–Posttest Design. The sample consisted of 28 first-grade students selected through saturated sampling. Data were collected through tests, observations, and documentation. Data analysis included descriptive statistics, the Shapiro–Wilk normality test, and the Paired Sample t-test. The findings indicated that the average pretest score of 60 increased to 75 on the posttest, while learning mastery improved from 42.86% to 75.00%. The hypothesis test produced a significance value (Sig. 2-tailed) of 0.000 (<0.05), indicating that the use of the maze board learning media had a significant positive effect on students' mathematics learning outcomes in the topic of vertical addition.